(untitled) (PerCursos, 2023)
Geological heritage, understood as an emerging concept, has expanded considerably in academic debate since the 1990s. However, it is commonly taken as an autonomous object to other heritage categories, such as natural and cultural. In addition, attempts to make it more integrated to society in general remain constant, seeking ways to “translate” the geological language to the general public. Taking these issues into consideration, this article aims to discuss the concept of geological heritage and its meanings, proposing an interpretation that highlights its links and connections with the so-called cultural heritage, and that considers it beyond the geological object itself. To accomplish this goal, the article is based on a theoretical and qualitative research that starts with a historical review of the term "heritage" and searches in its roots for data to think about the way it is contemporarily interpreted. Then, the emergence of geological heritage and its deep relations and convergences with the so-called cultural heritage are explored. Finally, it is exposed a brief resumption of the Brazilian experiences with the seal of Cultural Landscape and its affinity with the themes of Geoparks and geological heritage.